Differences in Skills of Pregnant Women in the Third Trimester Before and After Being Given Guidance on Breastfeeding Techniques - Dewa Ayu Wahyuli Indrayani; Ni Komang Erny Astiti; Ni Nyoman Suindri (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Breastfeeding technique is one of the factors that can influence breast milk production. Health guidance methods can increase the knowledge and skills of pregnant women in preparation for providing breast milk to their future babies. The aim of this research was to determine the differences in the skills of third trimester pregnant women before and after being given guidance on breastfeeding techniques at the Regional Level Implementation Unit of the Klungkung I Community Health Center. The type of research used was one group pretest-posttest. This research was carried out on April 11-May 11 2023 by means of purposive sampling. The population was 44 people and the sample was 32 people. The research instruments are in the form of observation sheets, Extension Event Units and Operational Procedure Units. Data were analyzed using the Wilcoxon Signed Rank Test. There is a difference in the skills of pregnant women in the third trimester before and after being given guidance on breastfeeding techniques with a p-value of 0.000<0.05. Midwives are expected to be able to provide information on the importance of the benefits of breast milk for babies.